A colorimetric and ratiometric fluorescence probe for rapid detection of SO2 derivatives bisulfite and sulfite. (November 2016) - Xiang, Kaiqiang; Chang, Shunzhou; Feng, Jingjing; Li, Changjiang; Ming, Wei; Liu, Ziyan; Liu, Yunchang; Tian, Baozhu; Zhang, Jinlong
Abstract: As one of the main atmospheric pollutants, sulfur dioxide (SO2 ) can be easily inhaled and turned into sulfite and bisulfite, which is harmful to both human health and ecological environment. Therefore, it is of significance to develop an effective method to detect the trace SO2 derivatives—SO3 2− and HSO3 − . Herein, we synthesized a semi-cyanine-coumarin hybrid dye for detection of SO3 2− and HSO3 − . Based on the nucleophilic addition of HSO3 − /SO3 2− to the vinyl group, Probe 1 showed high response speed, selectivity, and sensitivity towards SO3 2− and HSO3 − . Upon addition of HSO3 − /SO3 2−, color obviously changes from blue to yellow which can be differentiated by naked eyes. Probe 1 displays colorimetric and ratiometric response toward HSO3 − and SO3 2− . The detection limit is as low as 27.6 nM and the signal-to-background ratio in fluorescence intensity can reach 35-folds. Moreover, Probe 1 showed high selectivity and anti-interference ability in the co-existence of the environmental and biologic species. Graphical abstract: Highlights: A colorimetric and ratiometric fluorescence probe for detecting SO3 2− and HSO3 − was synthesized. The Probe showed high response speed, selectivity, and sensitivity towards SO3 2− and HSO3 − . The Probe showed high anti-interference ability in the co-existence of other species. The detection is based on the nucleophilic addition of HSO3 − /SO3 2− to the vinyl group.